(untitled) (Research, Society and Development, 2020)
The general objective of this research is to analyze the inclusion of students with physical, auditory and visual deficiencies in the regular education of municipal schools in the city of Barreirinhas. This research had an exploratory character, with quantitative and qualitative approach. The methodology used in this research was: reading articles, monographs and books dealing with Special Education; interview with the coordinator of Special Education in the Municipal Education Department (SEMED); research in locus in the target schools of the research and tabulation of the information coming from this study. The research revealed the inefficiency of the Municipal Government of Barreirinhas / MA to promote a quality education for people with physical, hearing and visual disabilities. Thus, it is understood that the municipality of Barreirinhas needs to develop actions that aim to effectively include students with disabilities in the educational system, such as: school adaptations; purchase of materials for Specialized Educational Assistance (AEE); campaigns to combat the discrimination of students with specific educational needs among the teachers of the Municipal Education Network.